2022
DOI: 10.3390/ijms23168949
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Nanogels with Endothelin-1 and Bradykinin Receptor Antagonist Peptides Decrease Inflammatory and Cartilage Degradation Markers of Osteoarthritis in a Horse Organoid Model of Cartilage

Abstract: Osteoarthritis (OA) is a degenerative and heterogeneous disease that affects all types of joint structures. Current clinical treatments are only symptomatic and do not manage the degenerative process in animals or humans. One of the new orthobiological treatment strategies being developed to treat OA is the use of drug delivery systems (DDS) to release bioactive molecules over a long period of time directly into the joint to limit inflammation, control pain, and reduce cartilage degradation. Two vasoactive pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 55 publications
(73 reference statements)
0
7
1
Order By: Relevance
“…Additionally, media conditioned from MSCs primed with IL-1β triggered a significant increase in MMP1 and MMP13 mRNA levels and HtrA1 protein amounts, which could be attributed to the increase in the concentration of pro-inflammatory molecules observed in the CM. IL-1β is one of the major pro-inflammatory cytokines involved in OA pathogenesis and its potential to increase MMP1 and MMP13 levels in eAC cultures has already been demonstrated (Bourdon et al, 2021;Cullier et al, 2022). However, the same studies have shown that the addition of IL-1β to eACs tended to be associated with decreased levels of HTRA1, which was not observed in our experiments.…”
Section: Bm-msc Secretome Priming Improves the Eac Phenotypecontrasting
confidence: 47%
“…Additionally, media conditioned from MSCs primed with IL-1β triggered a significant increase in MMP1 and MMP13 mRNA levels and HtrA1 protein amounts, which could be attributed to the increase in the concentration of pro-inflammatory molecules observed in the CM. IL-1β is one of the major pro-inflammatory cytokines involved in OA pathogenesis and its potential to increase MMP1 and MMP13 levels in eAC cultures has already been demonstrated (Bourdon et al, 2021;Cullier et al, 2022). However, the same studies have shown that the addition of IL-1β to eACs tended to be associated with decreased levels of HTRA1, which was not observed in our experiments.…”
Section: Bm-msc Secretome Priming Improves the Eac Phenotypecontrasting
confidence: 47%
“…However, before assessing its clinical e cacy, its safety must be validated. The biocompatibility of the abovementioned functionalized nanogels has already been validated in a previous in vitro study in which nanogels showed no cytotoxic effects but rather sustained metabolic activity and proliferation of equine articular chondrocytes (19).…”
Section: Introductionmentioning
confidence: 77%
“…They were produced in aseptic conditions to ensure sterile, pyrogenfree nanogels of speci c physicochemical characteristics. A similar formulation was previously investigated in vitro (19) and was proven to be biocompatible with no cytotoxic effect and bene ce metabolic activity and proliferation of equine chondrocytes (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue engineering studies conducted since the emergence of ACT in 1994 by Brittberg ( Brittberg et al, 1994 ) led to the development of suitable biological substitutes and refinement of organotypic models by the group of M. Demoor* ( Demoor et al, 2014 ). These mini-tissues/organoids have been incorporated in some translational research studies by the same group* ( Desancé et al, 2018 ; Cullier et al, 2022 ) to develop cell-based and cell-free orthobiological therapeutic approaches. Therefore, some in vitro studies have been transposed from humans ( Legendre et al, 2013 ; Gómez-Leduc et al, 2016 ; Gómez-Leduc et al, 2017 ; Legendre et al, 2017 ) to horses ( Desancé et al, 2018 ) again by this group* to demonstrate the therapeutic potential of chondrocytes and stem cells for cartilage engineering in both species and to have the possibility to carry out preparatory work in horses before transposing it to humans.…”
Section: Tissue Engineering Strategiesmentioning
confidence: 99%